Fungal community change in selected fluvisols under simulated flooding condition - Furtak, Karolina; Grządziel, Jarosław (Polish Journal of Agronomy, 2023)
The soil mycobiome is an important part of the numerous biogeochemical processes taking place in the soil. Its activity and diversity are influenced by many factors, including soil moisture. In this study, the effect of a 14-day simulated flood on the mycobiome of three different Fluvisols in microcosm experiment was assessed using next-generation sequencing. The results obtained showed that excessive moisture alters the structure of the mycobiome and the amounts of pathogenic, parasitic, and endophytic fungi. Among others, an increase in the occurrence of saprotrophic fungi of the genera Trichoderma, Talaromyces, and Schizothecium was noted. At the same time, the study showeda decrease in the abundance of arbuscular mycorrhizal fungi from the phylum Glomeromycota and Mucoromycota as a result of flooding. In addition, the structure of the soil mycobiome has been shown to be closely related to soil type – statistically significant correlations of individual fungal genera with the clay and silt or sand content of the soil were obtained. Future research on the soil mycobiome under flooding conditions may help to understand changes in soil biogeochemical processes following flooding, the occurrence of which is increasing with climate change.